Mass mortality of Canthigaster rostrata at the northeast coast of the Yucatan Peninsula - Jordán-Garza, A. G.; Díaz-Almeyda, E. M.; Iglesias-Prieto, R.; Maldonado, M. A.; Ortega, J. (Coral reefs, 2009)
On Dec 2008 a mass-mortality event affecting the sharpnose puffer, Canthigaster rostrata, was observed at several locations along the northeast coast of the Yucatan Peninsula. Fishes were dissected for signs of disease on the skin and organs, but none was found.